Armadilha Gravid Aedes Trap (GAT): videoanálise do seu mecanismo de funcionamento e seu uso como ferramenta de monitoramento de Aedes aegypti - Hilcielly Antunes Silva (2021)
The Gravid Aedes Trap (GAT) is a specific and efficient trap to capture gravid Aedes aegypti seeking for breeding sites, which has been used as a promising tool to replace, or complement, the conventional strategies used by vector surveillance programs (larval survey and ovitraps). This study aimed to evaluate GAT as a monitoring method and was divided into two chapters. In the first chapter, the goal was to evaluate the behavior of gravid Ae. aegypti from attraction to capture in the trap. Recording experiments and video analysis of mosquito behavior were performed in a large screened cage, under laboratory conditions, using the trap baited either with (a) water, (b) grass infusion or (c) synthetic oviposition attractant. Ethograms showed patterns of behavior sequence, which the main activities were: flight towards the GAT, touching and landing on certain parts and entering the trap. Traps baited with olfactory stimuli (grass infusion and synthetic attractant) significantly increased the movement and capture of mosquitoes (p<0.03), whose “spiral” flight behavior to enter the trap occurred in 70% of the captures. The second chapter evaluated the use of GAT to monitor and assess the population dynamics of Ae. aegypti at the Pampulha campus of the Federal University of Minas Gerais. Across the campus, 168 traps were installed and georeferenced, which were inspected weekly during 2017 to 2019. Caught mosquitoes were identified by sex and species and the data collected were made available on the internet in the MI-Aedes system. Maps and graphs of entomological indices weekly produced showed the abundance and distribution of Ae. aegypti, which were used to conduct vector control on campus. Vector monitoring showed a seasonal pattern in the population density of Ae. aegypti, with the period of greatest abundance occurring between September and January and the least abundant between May and August. In 2017 and 2018, higher entomological indices and “hotspots” of Ae. aegypti were obtained at the Veterinary School. However, in 2019, mosquito control activities (container larvicide treatment and insecticide spraying) were carried out, resulting in a significant reduction in the population of Ae. aegypti in the area during the period. The study findings elucidate the mechanisms involved in the attraction and capture of gravida Ae. aegypti by GAT, which in addition to contributing to the understanding of the oviposition behavior of the vector, can also be used to propose improvements in the trap and enhance its effectiveness. In addition, it was also demonstrated the effectiveness of the trap in monitoring and identifying areas infested by Ae. aegypti, providing necessary information to guide vector control activities.